Investigation of de novo cholesterol synthetic capacity in the gonads of goldfish (Carassius auratus) exposed to the phytosterol beta-sitosterol - MacLatchy Deborah L; Drolet Melissa; Sharpe Rainie L (BMC, 2006)
Abstract Total and intra-mitochondrial gonadal cholesterol concentrations are decreased in fish exposed to the phytoestrogen beta-sitosterol (beta-sit). The present study examined the potential for beta-sit to disrupt de novo cholesterol synthesis in the gonads of goldfish exposed to 200 microgram/g beta-sit and 10 microgram/g 17beta-estradiol (E2; estrogenic control) by intra-peritoneal Silastic® implants for 21 days. The de novo cholesterol synthetic capacity was estimated by incubating gonadal tissue with 14C-acetate for a period of 18 hours, followed by chloroform/methanol lipid extraction and thin layer chromatography (TLC) lipid separation. Lipid classes were confirmed using infrared spectroscopy. Plasma testosterone (T) and total cholesterol concentration were measured and gonadosomatic index (GSI) was calculated. Plasma T was significantly reduced in male beta-sit-treated fish compared to control and E2-treated fish (p < 0.001). 14C-Acetate incorporation into cholesterol and cholesterol esters was not significantly different among treatment groups for male and female fish, however, 14C-enrichment was higher than expected in both triglycerides (TG) and free fatty acids (FFA). FFA incorporation was significantly higher in male control fish than either beta-sit or E2 treatments (p = 0.005). Plasma cholesterol concentration was significantly increased in the male beta-sit treatment group compared to controls (p = 0.027). These results indicate gonadal de novo cholesterol biosynthetic capacity is not disrupted by beta-sit or E2 treatment in early recrudescing male or female goldfish, while plasma cholesterol and steroid concentrations are sensitive to beta-sit exposure.